A model for ERD2 function in higher plants - Robinson, David G.; Aniento, Fernando (Frontiers in plant science, 2020)
ER lumenal proteins have a K(H)DEL motif at their C-terminus. This is recognized by the ERD2 receptor (KDEL receptor in animals), which localizes to the Golgi apparatus and serves to capture escaped ER lumenal proteins. ERD2-ligand complexes are then transported back to the ER via COPI coated vesicles. The neutral pH of the ER causes the ligands to dissociate with the receptor being returned to the Golgi. According to this generally accepted scenario, ERD2 cycles between the ER and the Golgi, although it has been found to have a predominant Golgi localization. In this short article, we present a model for the functioning of ERD2 receptors in higher plants that explains why it is difficult to detect fluorescently tagged ERD2 proteins in the ER. The model assumes that the residence time for ERD2 in the ER is very brief and restricted to a specific domain of the ER. This is the small disc of ER immediately subjacent to the first cis-cisterna of the Golgi stack, representing specialized ER export and import sites and therefore constituting part of what is known as the “secretory unit“, a mobile aggregate of ER domain plus Golgi stack. ERD2 molecules in the ER domain of the secretory unit may be small in number, transient and optically difficult to differentiate from the larger population of ERD2 molecules in the overlying Golgi stack in the confocal microscope.
Gesehen am 07.01.2021